Price Spread Analysis of Mango in Southern Mindanao, Philippines - Aguinaldo, R.; Digal, L.; Sarmiento, Jon; Balgos, C. (International Society for Horticultural Science, 2013)
A price spread is the difference in the value of a product at two levels in the marketing chain. It reflects the margins and costs incurred at each node in the marketing chain. This study seeks to examine the behaviour of price spreads across the Southern Mindanao mango supply chain, identify the factors affecting price spreads, and examine the shares received at each node in the chain. Results show that farm prices are generally decreasing faster relative to wholesale and retail prices. The share of farm gate price to retail price is also decreasing over time. Results show that retailers accumulate the highest share. This reflects the high costs incurred at the retail level, which are attributed to the high wastage rate. An analysis of price spreads show that farmers receive the least benefit among the actors in the chain.